Preliminary results of a search for radio halos in starburst galaxies - Galante, Camila Ailen (2023)
Starburst galaxies undergo intense episodes of star formation. In these galaxies, gas is ejected into the surroundings in the form of strong winds, produced by the combined effect of numerous supernova explosions. When these winds interact with the intergalactic medium, they give rise to strong shocks that are capable of accelerating cosmic rays. The radiation from these rays in radio wavelengths is generated by synchrotron mechanism and can be detected when the galaxies are seen "edge-on" (i.e., its inclination is ∼90° with the line of sight). In this work, we investigate a sub-sample of edge-on galaxies in the MeerKAT 1.28 GHz Atlas of Southern Sources in the IRAS Revised Bright Galaxy Sample. To carry out an analysis of individual galaxies that allows us to find radio emission outside the galactic disk attributable to the presence of the wind, a software was developed and tested, which we detail in this work. We present here the results obtained using this software for a sub-group of galaxies that have been studied in the past using low-resolution observations, and we compare both results.